Manufacturing emerging economy firms in export markets - Shim, Yong Ju (2016)
This paper provides a new perspective on how manufacturing emerging economy firms (EEFs) achieve superior export performance. Unlike manufacturing developed economy firms that lack endowment problems, manufacturing EEFs only reach external markets by adding external resources (government support via subsidies) to their internal resources (R&D capabilities) to influence their internal environment (international patent production and export strategy development). I investigate 140 firms from four countries (Brazil, Russia, India and China) between 2008 and 2012 with data from an online survey. I establish relationships between the variables to guide the empirical development with structural equation modeling.